2021
DOI: 10.1016/j.ajem.2020.07.058
|View full text |Cite
|
Sign up to set email alerts
|

Unenhanced computed tomography (CT) utility for triage at the emergency department during COVID-19 pandemic

Abstract: Background Unenhanced chest computed tomography (CT) can assist in the diagnosis and classification of coronavirus disease 2019 (COVID-19), complementing to the reverse-transcription polymerase chain reaction (RT-PCR) tests; the performance of which has yet to be validated in emergency department (ED) setting. The study sought to evaluate the diagnostic performance of chest CT in the diagnosis and management of COVID-19 in ED. Methods This retrospective single-center st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…An example of such an adjudication committee is reported in a study where five board-certified specialists in respiratory and internal medicine were retrospectively invited to make a final diagnosis for each patient suspected of COVID-19. [30] In a similar study, all patients with a positive chest CT, but a negative RT-PCR, were discussed in a multidisciplinary meeting to arrive at a final diagnosis. [31] Panel-based diagnosis has the advantage of reflecting clinical settings, where it is common practice that difficult cases are examined during multidisciplinary meetings.…”
Section: Potential Solutions In the Absence Of Reliable Reference Standard For Covid-19mentioning
confidence: 99%
“…An example of such an adjudication committee is reported in a study where five board-certified specialists in respiratory and internal medicine were retrospectively invited to make a final diagnosis for each patient suspected of COVID-19. [30] In a similar study, all patients with a positive chest CT, but a negative RT-PCR, were discussed in a multidisciplinary meeting to arrive at a final diagnosis. [31] Panel-based diagnosis has the advantage of reflecting clinical settings, where it is common practice that difficult cases are examined during multidisciplinary meetings.…”
Section: Potential Solutions In the Absence Of Reliable Reference Standard For Covid-19mentioning
confidence: 99%
“…During chronic lung inflammation, the activity of neutrophils exclusively relies on anaerobic glycolysis, leading to increased glucose consumption and the uptake of FDG. Also, granulocytes and macrophages effectively facilitate glucose transport under chronic inflammatory conditions [67,68]. Amini et al reported a case of an 82-year-old man with a history of colon cancer, who complained of myalgia and fatigue for 10 days.…”
Section: Conventional Ctmentioning
confidence: 99%
“…Chest CT, due to its high sensitivity and widespread availability, is considered to be an effective tool to support the diagnosis of COVID-19 pneumonia with high or intermediate clinical probability, since it allows a rapid diagnostic workflow in emergency triage and may partially overcome the long turnaround time of RT-PCR [ 11 , 94 , 95 , 96 , 97 , 98 , 99 ]. In the emergency setting, patients with CT findings typical of COVID-19 pneumonia can be promptly isolated.…”
Section: Chest Ctmentioning
confidence: 99%
“…In the emergency setting, patients with CT findings typical of COVID-19 pneumonia can be promptly isolated. However, a study by Skalidis et al [ 97 ] showed that CT did not modify the estimated probability of COVID-19 infection and RT-PCR testing is generally required to confirm the diagnosis [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 22 , 23 ]. With the use of RT-PCR as the gold standard tool, chest CT usually showed greater than 90% sensitivity, with low to moderate specificity values ranging between 25 and 56% [ 8 , 100 ].…”
Section: Chest Ctmentioning
confidence: 99%